MAKNA DALAM NOVEL AKU TAK MEMBENCI HUJAN KARYA SRI PUJI HARTINI KAJIAN SEMIOTIK ROLAND BARTHES - Asmin; La Ode Syukur; Sri Suryana Dinar; Wa Ode Fitriani Sari (PT. CASA CENDEKIA MEDIA, 2025)
This study aims to reveal the meanings contained in the novel Aku Tak Membenci Hujan by Sri Puji Hartini using Roland Barthes' semiotic approach. One of the benefits of this research is to serve as a reference for future studies, particularly those concerning the application of Barthes' five codes in literary texts. This is a library research supported by primary data from the novel Aku Tak Membenci Hujan and secondary data from relevant literature. The method used is descriptive qualitative. The data source of this research is the novel Aku Tak Membenci Hujan by Sri Puji Hartini, published by Akad X Skuad in 2023, consisting of 348 pages. The data are in the form of written excerpts from the novel that contain elements of Barthes semiotic codes. The data were collected using reading and note-taking techniques. Data analysis was carried out using Roland Barthes' semiotic approach through five codes: hermeneutic, proairetic, semic, symbolic, and cultural codes.he results show that these five semiotic codes create a complex web of meaning in the novel's narrative, including mysteries within the story, sequences of actions, character representations, life symbols, and embedded cultural values. Through Barthes' semiotic perspective, readers are invited to uncover the latent meanings hidden beneath the surface of the text.